Silibinin releasing mesoporous bioactive glass nanoparticles with potential for breast cancer therapy - Nawaz, Qaisar; Fuentes-Chandía, Miguel; Tharmalingam, Varun; Ur Rehman, Muhammad Atiq; Leal-Egaña, Aldo; Boccaccini, Aldo R. (Ceramics International, 2020)
Mesoporous materials have attracted extensive consideration in the field of drug delivery. The targeted release of anti-neoplastic agents depends on the carrier used to transport such drugs in the body. In this study, mesoporous bioactive glass nanoparticles (MBGN) of an average size of 120 ± 10 nm were used to load and release silibinin, which is a natural flavonolignan used as anticancer agent and tumor suppressor. Mesoporous bioactive glass nanoparticles were characterized in terms of morphology and release potential after being loaded with silibinin. The loading and release amounts of silibinin were quantified using UV-VIS spectrophotometer at λmax = 280 nm in PBS buffer solution (pH 7.4). It was found that MBGN have a maximum loading efficiency of 61% against optimal silibinin concentration (i.e. 40 μg/ml silibinin in PBS buffer solution (pH 7.4)). The drug was released in a sustained manner from loaded mesoporous bioactive glass nanoparticles and a release of 18 μg/ml silibinin was measured during the first 24 h post-drug loading. Further, the chemotherapeutic effect of silibinin was tested on metastatic MDA-MB-231 breast cells and the non-metastatic breast cell line MCF-10A at two different concentrations (9.0 μg/ml and 18 μg/ml). As our results show, silibinin exhibits a chemotherapeutic potential towards MDA-MB-231 cell line, which is a much lower concentration compared to values reported in literature. According to our knowledge, this is the first study elucidating the use of MBGN as a carrier for silibinin, as well as testing its lethal effect in contact with breast neoplastic cells. Taken collectively, the results of the present study suggest that silibinin-loaded MBGN can be applied as an effective drug delivery system to cause a chemo preventive response which has the potential to be beneficial for the treatment of breast cancer.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Antineoplastic drug carrier; Bioactive glass; Biomaterials for cancer research; Drug delivery system; Mesoporous nanoparticles; Silibinin